Fifty key video games - Perron, Bernard; Boudreau, Kelly; Arsenault, Dominic; Wolf, Mark J. P. (Routledge, an imprint of the Taylor & Francis Group, 2023)
"This volume examines fifty of the most important video games that have contributed significantly to the history, development, or culture of the medium, providing an overview of video games from their beginning to the present day. This volume covers a variety of historical periods and platforms, genres, commercial impact, artistic choices, contexts of play, typical and atypical representations, uses of games for specific purposes, uses of materials or techniques, specific subcultures, repurposing, transgressive aesthetics, interfaces, moral or ethical impacts, and more. Key video games featured include Animal Crossing, Call of Duty, Grand Theft Auto, Legend of Zelda, Minecraft, PONG, Super Mario Bros., Tetris, and World of Warcraft. Each game is closely analyzed in order to properly contextualize it, to emphasize its prominent features, to show how it creates a unique experience of gameplay, and to outline the ways it might speak about society and culture. The book also acts as a highly accessible showcase to a range of disciplinary perspectives that are found and practiced in the field of game studies. With each entry supplemented by references and suggestions for further reading, Fifty Key Video Games is an indispensable reference for anyone interested in video games"--Provided by publisher.